2022
DOI: 10.3390/antiox11050876
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic and Prophylactic Potential of Quercetin against COVID-19: An Outlook on the Clinical Studies, Inventive Compositions, and Patent Literature

Abstract: Quercetin is a phenolic flavonol compound with established antioxidant, anti-inflammatory, and immuno-stimulant properties. Recent studies demonstrate the potential of quercetin against COVID-19. This article highlighted the prophylactic/therapeutic potential of quercetin against COVID-19 in view of its clinical studies, inventions, and patents. The literature for the subject matter was collected utilizing different databases, including PubMed, Sci-Finder, Espacenet, Patentscope, and USPTO. Clinical studies ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 40 publications
0
45
0
Order By: Relevance
“…The infection with SARS-CoV-2 (a RNA virus) causes contagious COVID-19, which has disastrously impacted the world’s demography [1] . The first case of COVID-19 emerged in December 2019, whereas the World Health Organization (WHO) announced it as a pandemic in March 2020 [1] , [2] , [3] . SARS-CoV-2 is transmitted through the respiratory droplets of the infected person and virus-contaminated surfaces/items [1] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The infection with SARS-CoV-2 (a RNA virus) causes contagious COVID-19, which has disastrously impacted the world’s demography [1] . The first case of COVID-19 emerged in December 2019, whereas the World Health Organization (WHO) announced it as a pandemic in March 2020 [1] , [2] , [3] . SARS-CoV-2 is transmitted through the respiratory droplets of the infected person and virus-contaminated surfaces/items [1] .…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 is transmitted through the respiratory droplets of the infected person and virus-contaminated surfaces/items [1] . The general symptoms of COVID-19 include fever, cough, sore throat, nasal congestion, headache, fatigue, pain in muscles/joints, loss of smell/taste, diarrhea, and breathlessness [1] , [2] , [3] , [4] . Most of the COVID-19 patients (about 80%) recover without hospitalization, about 15% get serious symptoms, and about 5% require intensive care [1] , [2] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, quercetin suppresses inflammation through interference in various signaling pathways, especially NF-κB [ 176 ]. With regard to human studies, the interim results from one RCT that demonstrated that quercetin supplementation improved viral clearance and partially lowered symptoms severity [ 177 ]. In another RCT, the therapeutic efficacy of quercetin was evaluated in combination with antiviral drugs in hospitalized COVID-19 patients, showing that it diminished the hospitalization period.…”
Section: Nutraceuticals and Dietary Supplements Against Covid-19 Dise...mentioning
confidence: 99%